Effect of ridge-furrow with plastic mulching and organic amendment on fertilizer-N fate in maize-soil system: A 15N isotope tracer study - Meng, Qiang; Liu, Jingxia; Cao, Zhixiang (Frontiers in Environmental Science, 2024)
The implementation of ridge-furrow with plastic film mulching has the potential to enhance crop yields and water productivity, particularly in black soil regions. However, the synergistic impacts of combining ridge-furrow with plastic mulching alongside with various organic amendments on maize yield and nitrogen fertilizer utilization efficiency remain unclear. Using 15 N-labeled tracing technology, we investigated fertilizer-N recovery of maize, distribution, fertilizer-N residual in soil, and nitrogen fertilizer loss across six treatments: non-mulched flat with non-organic amendment (FN), non-mulched flat with straw amendment (FS), non-mulched flat with biochar amendment (FBC), ridge-furrow with plastic mulching without organic amendment (RN), ridge-furrow with plastic mulching with straw amendment (RS), and ridge-furrow with plastic mulching with biochar amendment (RBC). The results revealed that ridge-furrow with plastic mulching in comparison to non-mulched flat, led to a significant increase in maize dry biomass accumulation, yield, and the rate of fertilizer-N recovery in maize (NRE) by 8.57-12.36%, 10.08-15.13%, and 2.22-3.18%, respectively. The rate of fertilizer-N residual in soil (NSR) and fertilizer-N loss (NLS) decreased by 0.5-2.04% and 0.78-3.21%, respectively. In addition, the straw and biochar amendments under different planting methods promoted NRE in plants and NSR in soil, reducing NLS. Compared with non-organic amendment treatments, the inclusion of straw and biochar amendments resulted in increased NRE and NRS by 1.64-6.20% and 0.12-2.18%, while NLS decreased by 1.76-7.78%. Biochar amendment treatment exhibited significantly higher nitrogen accumulation and NRE compared to the straw amendment treatment. Overall, ridge-furrow with plastic mulching combined with biochar amendment proved to be an effective method to enhance nitrogen fertilizer utilization of maize in the black soil regions, improving both yield and nitrogen fertilizer utilization efficiency.